Imitatio christianorum the function of believers as examples in Philippians - Cable, Paul S. (2016)
In Philippians, Paul has pastoral, paraenetic aims: the Philippians are to adopt a Christian phronesis - a way of thought and life determined by their relationship to the crucified, humiliated, and risen Christ consisting specifically, in Philippians, of (1) an others-focused mindset; and (2) an attendant boldness and willingness to accept suffering and the burdens of others on behalf of the progress of the gospel. These paraenetic emphases are then embodied and illustrated by multiple examples: Christ is the ultimate exemplar and the source of the content of the exhortation. Paul himself is also one who embodies these qualities, though imperfectly. Timothy especially exemplifies others-focus, and Epaphroditus the willingness to suffer in the service of Christ. Euodia and Syntyche, finally, serve Christ boldly but lack the others-focus and unity that Paul exhorts. We conclude, then, that Paul understands the provision of such Christ-like examples and the imitation of those examples by those in Christ within Christian communities to be an important means by which the community progresses in holiness, that is, to be increasingly conformed to Christ.
Keywords: Bible. Philippians; Jesus Christ; Paraenesis; Paul, Saint, Apostle; Role models; Suffering -- Religious aspects -- Christianity; Timothy, Saint; Peer reviewed